Analysis of Roles and Functions of Islamic Centers as Hubs: Three Locations Case Study - Ananda, Rauzah Nahwa; Bahri, Samsul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The Islamic Center stands as a multifaceted complex of Islamic facilities, strategically designed to function as a central hub for a wide array of religious and community needs. Its role extends significantly beyond that of a traditional mosque, offering dedicated spaces that foster comprehensive religious learning, encourage vibrant community interaction, and promote social development, all deeply rooted in core Islamic values. This study undertakes a thorough analysis of the diverse functions and critical roles performed by Islamic Centers. Employing a comparative case study approach, it examines three distinct locations, each characterized by unique facility configurations and varying patterns of religious activities. This methodology aims to achieve a holistic understanding of the operational dynamics of Islamic Centers and the specific community needs they effectively address.The core of the analysis is dedicated to identifying the essential facilities that underpin the successful operation of these centers. It further investigates the prevailing structures of activities organized within them and assesses their tangible contributions to both religious enrichment and broader social development within their respective communities.The findings derived from this research offer valuable insights into the fundamental components necessary for establishing and maintaining an effective Islamic Center. These essential elements include adequate worship spaces, robust educational facilities, well-developed da’wah (outreach) infrastructure, accessible social areas, and dedicated spaces for community empowerment initiatives. Collectively, these components form the foundational framework for planning Islamic Centers that are not only comprehensive and adaptive to evolving societal needs but also deeply relevant to their specific local contexts.